Pelatihan Pembuatan Sabun Daun Suruhan/Sirih Cina (Peperomia Pellucida L.Kunth) bagi Kelompok PKK Dusun Cekelen, Karangsari - Marliati, Nolis; Siregar, Ika Pranita; Tarigan, Christine Ulina (Jurnal ETAM, 2023)
Training on making Suruhan leaf soap which was carried out in the community, especially the PKK group in the Cekelan hamlet, Kapenawon Pengasih, Kulon Progo, aims to: 1) Increase motivation in creating entrepreneurs to improve the family economy, 2) Increase knowledge and skills in making soap from suruhan leaves, 3) Provide inspiration and motivation from the skills possessed to create soap from other plants that have their own uniqueness and high selling value. The method used begins with the socialization of the program, the preparation stage, the implementation stage which includes lectures, demonstrations, exercises or practices and the mentoring and evaluation stages. The results obtained are an increase with an average increase in participant achievement of around 48.75%. This means that the knowledge of the trainees about soap and how to make it has increased so that overall the initial objectives of this activity have been achieved. The increase in the knowledge of PKK mothers is expected to motivate in improving community welfare and eradicating unemployment.